Unlocking the Role of Actor Networks and Strategies for Developing Collaborations in Regional Featured MSEs - Suryawati, Dina; Helpiastuti, Selfi Budi; Suji, Suji; Supranoto, Supranoto; Molasy, Honest Dody; Firdaus, Alfareza; Hidayah, Nurussyamsil (Puslatbang KDOD Lembaga Administrasi Negara, 2025)
The crisis has raised concerns about behavioral adaptation and resilience changes in micro and small enterprises (MSEs). As a result, MSEs need to get policy support by determining policy strategies oriented towards collaboration schemes. This study explores the actor network of MSEs of regional superior products and determines the right policy strategy to encourage a broader and more sustainable collaboration process. This study contributes to creating collaborative policy strategy directions for SMEs by utilizing actor networks. This research focuses on elaborating the concepts of network governance and collaborative governance. The study employed a descriptive qualitative method through empirical mapping of MSE stakeholder actors using Miro Apps. Data was analyzed using IFAS-EFAS techniques to determine suitable strategies for supporting MSE policies. The results show the dynamics and complexity of the MSE network with its main vital actors: state andnon-state actors. Strategic efforts can be realized through rotation functions to achieve a productive economy by optimizing the potential for adaptive collaboration through MSE policies on superior products by minimizing existing weaknesses